Revitalization of Gotong Royong Culture as a Strategy to Maintain the Cleanliness and Health of the Community Environment - Mochamad Fikri Rili Alamsyah; Marwa Sagita; Neng Anisa Aulia; Isnu Ardi; Nurul Siti Nurjanah; Salwa Nur Putri Hanslie; Adi kusnadi; Nursyifa Utami; Muhammad Zaky; Tina Septiana (Siber Nusantara of Community Service Review, 2026)
The problem of environmental cleanliness is still a challenge in various residential areas, including in Sukakarya Village. Poorly maintained environmental conditions, such as the accumulation of household waste, clogged drainage channels, and decreased community participation in community service activities, have the potential to have a negative impact on public health and environmental quality. One of the strategic efforts that can be carried out is the revitalization of the culture of mutual cooperation as a form of strengthening the collective participation of the community in maintaining environmental cleanliness. This Community Service (PKM) activity aims to increase public awareness, strengthen social participation, and create a clean and healthy environment through the strengthening of the culture of mutual cooperation. The method used in this activity is Participatory Action Research (PAR) with the stages of problem identification and field observation, Forum Group Discussion (FGD), implementation of mutual cooperation actions, community education, and evaluation of activities. The results of the activity show that the gotong royong revitalization program is able to increase community participation in environmental cleanliness activities, improve the physical condition of the environment through cleaning residential areas and drainage channels, and increase public awareness of the importance of maintaining environmental cleanliness and health. In addition, this activity also strengthens social solidarity and rebuilds the values of togetherness in community life. Thus, the revitalization of the gotong royong culture has proven to be an effective strategy in managing environmental cleanliness based on community participation and has the potential to become a model of sustainable community empowerment.